Teaching medical humanities in the digital world: affordances of technology-enhanced learning - Kemp, Sandra; Day, G. (BMJ, 2014)
Medical humanities courses are typically taught in face-to-face teaching environments, but now medical humanities educators, alongside educators from other disciplines, are facing shifts in higher education towards online (and sometimes open) courses. For the medical humanities educator, there is limited guidance regarding how technology-enhanced learning design can support the learning outcomes associated with medical humanities. This article aims to provide useful direction for such educators on how digital technologies can be used through learner-focused pedagogies. Specific examples are provided as to how the affordances of Web 2.0 and other tools can be realised in innovative ways to help achieve skills development within the medical humanities. The guidance, alongside the practical suggestions for implementation, can provide important conceptual background for medical humanities educators who wish to embrace technology-enhanced learning, and reconceptualise or redesign medical humanities for an online or blended teaching environment.